2019
DOI: 10.1021/acs.langmuir.9b00756
|View full text |Cite
|
Sign up to set email alerts
|

Small-Angle X-ray Scattering Studies on the Structure of Disc-Shaped Bicelles Incorporated with Neutral PEGylated Lipids

Abstract: In this study, small-angle X-ray scattering (SAXS) is successfully employed to investigate the structure of the DPPC/diC7PC disc-shaped bicelles incorporated with different amounts of C16-PEG2000-Ceramide lipids. The incorporation of the C16-PEG2000-Ceramide lipids could provide an antifouling capability to the bicelle for biomedical applications. However, traditionally it is believed that most of the incorporated PEGlylated lipids should lie in the rim of the disc-shaped bicelle. In this study, high sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 52 publications
(93 reference statements)
0
13
0
Order By: Relevance
“…Due to the increased size of the headgroup in such cases, PEGylated lipids can assume a more cone‐like appearance than typical long‐chain phospholipids and may locate in the edge and/or planar regions of a bicelle disk. [ 197 ]…”
Section: Lipid Bicellesmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the increased size of the headgroup in such cases, PEGylated lipids can assume a more cone‐like appearance than typical long‐chain phospholipids and may locate in the edge and/or planar regions of a bicelle disk. [ 197 ]…”
Section: Lipid Bicellesmentioning
confidence: 99%
“…[ 203 ] While PEGylated lipids have a mainly cone‐like geometry, more detailed structural studies have shown that a neutral PEGylated lipid (C16‐PEG2000‐ceramide) can distribute across both the planar region and rims of bicellar disk. Of note, there is indeed an approximately, two‐fold greater density of PEGylated lipids in the rims, [ 197 ] however, it should also be noted that the broader distribution of the PEGylated lipid is advantageous for potential in vivo applications. In molecular dynamics simulations, it has also been shown that bicelles containing ligand‐modified PEGylated lipids are more easily internalized by cells than similarly functionalized liposomes due to more favorable membrane energetics [ 204 ] (see also other examples of bicelles with improved cellular uptake properties over liposomes [ 205 ] ).…”
Section: Lipid Bicellesmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In some lipid systems, for instance, the assembly structures are important to the study of the interaction of membranes and assist the simulating membrane template for accommodating membrane proteins. 22,23 Even some in vitro drug release and diffusion experiments have shown that the drug release rate is faster in the cubic phase than in the hexagonal phase. 1,24 Inside the reverse cubic structure, water channels are continuous but nonintersecting.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Different micelle packings establish different delivery paths for the drugs and even the drug encapsulation capability, which is significantly related to the performance of drug release . In some lipid systems, for instance, the assembly structures are important to the study of the interaction of membranes and assist the simulating membrane template for accommodating membrane proteins. , Even some in vitro drug release and diffusion experiments have shown that the drug release rate is faster in the cubic phase than in the hexagonal phase. , Inside the reverse cubic structure, water channels are continuous but nonintersecting . However, water channels in the reversed hexagonal phase are smaller in diameter and close to each other with a large interfacial curvature .…”
Section: Introductionmentioning
confidence: 99%